Membangun Kesiapan Mental, Spiritual, dan Sosial Remaja Usia Nikah melalui Program Keluarga Sakinah Maslahah - Wiwin Siti Aminah Rohmawati; Sumadi Sumadi (CV. Creative Tugu Pena, 2026)
Family is the fundamental pillar of a harmonious and prosperous society, yet many adolescents of marriageable age in Ciamis Regency lack adequate mental, spiritual, and social readiness to build a household. Early marriage, young divorce, and limited understanding of the concept of keluarga sakinah maslahah (a just, balanced, reciprocal, and beneficial family) remain pressing challenges. This community engagement program, initiated by the Ahwal Asyakhsiyyah Study Program, Faculty of Sharia and Law, Universitas Islam Darussalam Ciamis, aimed to enhance the understanding, awareness, and skills of marriageable-age youth in the Nahdlatul Ulama community of Ciamis regarding keluarga sakinah maslahah. The program applied an andragogical approach through four main activities: a two-day workshop, peer education, family counseling by religious extension workers, and a focus group discussion, involving 35 marriageable-age youths and 10 Islamic religious counselors as primary beneficiaries. Pre-test and post-test results showed significant improvement across all measured aspects, particularly regarding the concept of sakinah maslahah marriage and the foundations of family need fulfillment, alongside improved communication, conflict management, and financial management skills. Of the participants, 85.2% reported a change in their understanding of marriage, and 91.2% reported increased understanding of the sakinah maslahah family concept. As a follow-up, participants conducted peer education outreach to more than 100 other marriageable-age youths, demonstrating the program's sustainability through their commitment to continued learning and collaboration with various stakeholders. The outcomes of this program are expected to contribute to reducing divorce rates and strengthening family resilience in Ciamis Regency.